When Two Strong Men [or Women] Stand Face to Face - Stanley, Julian C. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
The speech given at the awards ceremony of the Midwest Talent Search Project, addresses gifted and talented students about issues in their education. The speaker urges students to be assertive in fighting curricular inflexibility and to understand the complementary functions of acceleration enrichment. He discusses the benefits of summer courses sponsored by the Study of Mathematically Precocious Youth. The paper concludes with 10 suggestions, including a justification of public school services for gifted and talented students, the importance of supplementary activities and summer residential academic courses, the value of college-level advanced placement examinations, the need for post-graduate education, and the opportunity to receive a well-rounded education. (CL)
ERIC Note: Paper presented at Awards Ceremony of the Midwest Talent Search Project (Evanston, IL, June 5, 1983).
Students.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum Development; Educational Needs; Enrichment; Gifted; Talent; Speeches/Meeting Papers; Guides, Non-Classroom.